2009
DOI: 10.3354/meps07793
|View full text |Cite
|
Sign up to set email alerts
|

Using active acoustics to compare lunar effects on predator–prey behavior in two marine mammal species

Abstract: Many delphinids feed on vertically migrating sound-scattering layers. The migration of micronektonic animals in these layers is strongly affected by light, both solar and lunar. Active acoustic approaches were used to observe lunar phase effects on the diel patterns of sound-scattering layers in 2 habitats and to simultaneously observe the behavior of foraging spinner dolphins Stenella longirostris in Hawaii and dusky dolphins Lagenorhynchus obscurus in New Zealand. Lunar phase was important in structuring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 51 publications
(52 reference statements)
0
27
3
Order By: Relevance
“…Hernandez-Milian et al (2008) showed significant positive relationships between moon phase and sightings of short-beaked common dolphin (Delphinus delphis, Linnaeus, 1758) and Atlantic spotted dolphin (Stenella frontalis, Cuvier, 1829) in the Azores. Although previous studies suggest that moon phase is likely to be important in determining behaviour of the many delphinid species that forage on vertically migrating prey (Hernandez-Milian et al, 2008;Benoit-Bird et al, 2009), our results show that the lunar phase is not correlated with dolphin interaction in these waters.…”
Section: Discussioncontrasting
confidence: 78%
“…Hernandez-Milian et al (2008) showed significant positive relationships between moon phase and sightings of short-beaked common dolphin (Delphinus delphis, Linnaeus, 1758) and Atlantic spotted dolphin (Stenella frontalis, Cuvier, 1829) in the Azores. Although previous studies suggest that moon phase is likely to be important in determining behaviour of the many delphinid species that forage on vertically migrating prey (Hernandez-Milian et al, 2008;Benoit-Bird et al, 2009), our results show that the lunar phase is not correlated with dolphin interaction in these waters.…”
Section: Discussioncontrasting
confidence: 78%
“…Risso's dolphins, Grampus griseus , a squid predator (Baird ), were detected frequently throughout the study area both visually and from the active acoustics. The unique echo characteristics of marine mammals (Benoit‐Bird et al ) make them easy to distinguish in echograms (Fig. D).…”
Section: Resultsmentioning
confidence: 99%
“…Single targets were extracted from both the 38 kHz and 120 kHz data. Echoes consistent with marine mammals were identified based on their frequency response, intensity, and morphology (Benoit‐Bird et al ), their positions noted, and their echoes removed from the dataset for further analyses of the scattering layer (Fig. A).…”
Section: Methodsmentioning
confidence: 99%
“…However, species of the deep scattering layers also react to changes in moonlight intensity, migrating closer to the surface during new moons than during full moons 8–11 . Such cyclical responses of mesopelagic organisms to moonlight are thought to induce significantly different foraging strategies in predators.…”
Section: Introductionmentioning
confidence: 99%